Representasi Gender Dalam Film Pendek Pria Karya Yudho Aditya: - Ginting, Sofhia Rahmadani; Saqina, Elsa Khoriah; Sazali, Hasan; Dalimunthe, Maulana Andinata (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Recently, film has often become a means of communication that is used to convey sensitive messages or even those that are difficult to convey clearly, but in accordance with the realities that exist in society. Therefore, this research was conducted to identify gender identity in the film "PRIA". The film "PRIA" itself tells about the life of a schoolboy who is quite different from his other friends. The main character named Aris has a different sexuality from his friends in general. He is gay, and Aris's mother certainly does not believe this, so she thinks that her child is sick. So he without thinking twice immediately matched his son with a woman in his village in the hope that his child would return to normal. Keywords: film, MEN, LGBT, Aris.